POLA INTERAKSI GURU DALAM PROSES PEMBELAJARAN IPS DI SMP N 1 SUNGAI RUMBAI - Mahturohmah, Fitri Anik (Pendidikan Sejarah, 2014)
In social studies learning process pattern of interaction is more dominant using one-way interaction concentrate centered on the teacher. This can be seen in the process of learning social studies in the classroom during a lesson that teacher a role active in the classroom, while the students just accept what is presented by the teacher. This conditions have an impact on the propensity of teachers in learning process. Ideally, the learning pattern is an effective interaction that involves students actively like asking, expression, idea / ideas and answered questions from the teacher. Purpose of the research to describe patterns of teacher interaction in the learning process of social studies teachers is the tendency of patterns of interaction in the learning process of social studies at SMP N 1 Sungai Rumbai. Kind of research that researcher is descriptive qualitative, with sites in SMP N 1 Sungai Rumbai Dharmasraya. The informan are teacher, the students of SMP N 1 Sungai Rumbai. data collection techniques are observation, interviews, documentation. These data were processed using triangulation is checking the validity of the data. Based on the result of the research showed that the tendency of teacher interaction patterns in social studies learning is a two-way interaction patterns and multi-direction. Two-way interaction pattern is by using a question and answer method, the pattern of two-way interaction between teachers and students are active in the learning process. Multi-directional interaction patterns by using methods discussion so that students are more active in the learning process, students are more confident in issuing opinions. Based on the results it can be concluded that the tendency of the interaction patterns in learning process used in teaching social studies is a two-way interaction patterns and multi-direction. Teachers have tried to involve students in the learning process. However, most of the students in the learning process there were not active and did not pay attention to the teacher when the teacher explains the subject matter.